The Use of Technology in Classroom Learning with Collaboration in Improving Students' Outcomes in India - Suyog Sunil Shinde, Dr Amit Medhekar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This quantitative study examines the impact of integrating technology in collaborative learning environments on student outcomes in Indian schools. Surveys were collected from students, teachers, parents, and administrators at 10 schools across India to understand how technology usage, collaborative learning activities, and their integration affect academic performance, student engagement, motivation, and 21st-century skills development. Key findings indicate that frequent technology use, particularly when integrated with collaborative learning, positively impacts academic achievement and student engagement. However, technical issues and lack of access to technology pose significant challenges. The study offers recommendations for educators and policymakers to enhance the effectiveness of technology-enhanced collaborative learning in India.